2023
DOI: 10.1136/bmjopen-2022-068518
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life and its determinants among patients with diabetes mellitus: a multicentre cross-sectional study in Northwest Ethiopia

Abstract: ObjectivesThis study assessed the health-related quality of life (HRQoL) and its determinants in patients with diabetes.Design and settingAn institutional-based multicentre prospective cross-sectional study design was conducted in diabetes follow-up clinics of selected hospitals in Northwest Ethiopia from April to July 2022.ParticipantsAll eligible adult patients with diabetes at the selected facilities.Main outcome measuresHRQoL was measured using EuroQol 5-dimensions 5-levels (EQ-5D-5L) and the EuroQol-Visua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Their finding demonstrated that those with more severe conditions tend to have lower satisfaction due to the high occurrence of symptoms [ 56 ]. Consistent with our finding, a study conducted among diabetic patients in Ethiopia also signifies that complications and multimorbidity were the key determinants of lower degree of treatment satisfaction [ 57 ]. Thus, further studies should focus on assessing this association to identify the actual basis between these variables among older adult patients.…”
Section: Discussionsupporting
confidence: 91%
“…Their finding demonstrated that those with more severe conditions tend to have lower satisfaction due to the high occurrence of symptoms [ 56 ]. Consistent with our finding, a study conducted among diabetic patients in Ethiopia also signifies that complications and multimorbidity were the key determinants of lower degree of treatment satisfaction [ 57 ]. Thus, further studies should focus on assessing this association to identify the actual basis between these variables among older adult patients.…”
Section: Discussionsupporting
confidence: 91%
“…Particularly in Ethiopian settings, most patients are of low socioeconomic status (67,68). On the contrary, most patients with chronic diseases have comorbid conditions and receive multiple medications (36)(37)(38)(39). Thus, patients with a lower income will have a lower level of medication adherence because most multimorbidity patients may be unable to afford treatment costs for multiple medications.…”
Section: Discussionmentioning
confidence: 99%
“…There is an increasing number of patients with multimorbidity in Ethiopia, and most patients with chronic diseases have at least one comorbid chronic condition with a high number of prescribed medications (36)(37)(38)(39). This could be attributed to the increasing complexity of medication regimens, which in turn impacts patients' medication adherence.…”
Section: Introductionmentioning
confidence: 99%
“…Participants who were not actively engaged in diabetes self-management exhibited lower health outcomes, including quality of life [ 34 ]. A study conducted among type 2 diabetes patients in Ethiopia indicated that a longer duration of DM negatively impacted patients’ quality of life, which may have been related to the discomfort of insulin injections or the pain associated with diabetes complications [ 35 ].…”
Section: Discussionmentioning
confidence: 99%